GURU PENDIDIKAN AGAMA KATOLIK IDEAL MENURUT DOKUMEN LAY CATHOLIC IN SCHOOLS - Fatlolon, Costantinus; Nurlatu, Monika (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2021)
Teachers of Catholic Religious Education (CRE) are essential to the educational process because they serve as witnesses and ambassadors of faith to students and the school community at large. However, as contemporary science and technology advance, this identity and role are progressively disappearing. Based on the teachings of the Catholic Church, as expressed in the document Lay Catholics in Schools: Witnesses to Faith, this article is literature research that attempts to bring this identity and role back to the highest awareness of lay CRE teachers. The article’s central query is: “What is the identity and role of Catholic Religious Education teachers according to the Document Lay Catholics in Schools: Witnesses to Faith?” This article offers an ideal model of CRE teachers are the primary and most important religious witnesses for the growth of the full person, students, other teachers, the school environment, and the public at large. They are significant not only because they communicate the doctrine of the Catholic Church and other educators but most importantly the teachings of Jesus Christ.